ANALYSIS OF FACTORS INFLUENCING THE MORTALITY RATE AMONG PATIENTS WITH POLYTRAUMA IN THE EARLY STAGE HOSPITALIZED IN REGIONAL MULTIDISCIPLINARY HOSPITAL - V. A. Porkhanov; A. A. Zavrazhnov; A. A. Afaunov; A. N. Blazhenko; M. L. Mukhanov (Медицинский вестник Юга России, 2016)
Objective: rate the importance of the factors affecting the level of mortality in polytrauma victims in the early posttraumatic period hospitalized in the regional multidisciplinary hospital. Material and methods: in this work is the analysis of treatment results of 3873 patients with polytrauma (NISS≥17), treated in Research Institute Regional clinical hospital №1 named after prof. C. V. Ochapovskiy in Krasnodar in the period from 2003 to 2014. During this time period the upgrading of the versatile hospital, reorganization scheme of assistance to victims with polytrauma within the hospital and development of a regional system of hospitalization. Results: the mortality among patients with polytrauma was decreased from 39.8% in 2003 to 8.1% in 2014. Conclusion: there are identified and evaluated eight factors that influenced the decline of mortality in patients with polytrauma.